USA Judo (2006)
USA Judo exists for the purpose of serving as the national governing body for the sport of judo in the United States in accordance with the Ted Stevens Olympic and Amateur Sports Act, 36 U.S.C. § 220501 et seq. (the "Sports Act") and, as such, to be a member of the United States Olympic Committee (the "USOC"). Mission. In furtherance of its purpose, the mission of USA Judo is to enable United States athletes to achieve sustained competitive excellence in domestic and international amateur judo competition and to promote and grow the sport of judo in the United States.